2017
DOI: 10.1177/2324709617744232
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tachycardia in Patients With Submassive Pulmonary Emboli to Risk Stratify for Early Initiation of Thrombolytic Therapy: A Case Series Comparing Early Versus Late Thrombolytic Initiation

Abstract: Pulmonary embolism (PE) represents a prevalent cause of morbidity and mortality in the United States, with approximately 600 000 cases diagnosed annually. The mortality rate for untreated PE is as high as 30%. Right ventricular (RV) dysfunction is a sign of possible adverse outcomes with right-sided heart failure being the usual cause of death from PE. There is a spectrum of clinical presentations associated with PE diagnoses, from incidental and asymptomatic to rapid hemodynamic collapse. Despite successes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This present study showed that asymptomatic young adults could have S1Q3T3 pattern which is also more prevalent in females. However, among the participants in this study, the electrocardiographic pattern was associated with normal heart rate unlike the clinical cases of pulmonary embolism usually characterized by tachycardia [28][29][30][31] . The finding of S1Q3T3 pattern among healthy young adults in this study was surprising because it is rarely reported in literature.…”
Section: Discussionmentioning
confidence: 53%
“…This present study showed that asymptomatic young adults could have S1Q3T3 pattern which is also more prevalent in females. However, among the participants in this study, the electrocardiographic pattern was associated with normal heart rate unlike the clinical cases of pulmonary embolism usually characterized by tachycardia [28][29][30][31] . The finding of S1Q3T3 pattern among healthy young adults in this study was surprising because it is rarely reported in literature.…”
Section: Discussionmentioning
confidence: 53%
“…[16] Accordingly, sustained tachycardia and normal blood pressure were observed in clinical settings. [17] In addition, the Wells score and revised Geneva score that were developed to predict the probability of PTE have heart rate (>100 and ≥ 95 beats/min, respectively) as one of the predictive variables. [8,9] Particularly, the heart rate of ≥95 beats/min has the highest score among the variables included in the revised Geneva score.…”
Section: Discussionmentioning
confidence: 99%
“…The increased afterload causes right ventricular dysfunction and dilatation that displace the interventricular septum towards the left leading to a reduction in cardiac output and systemic arterial blood pressure, which is compensated for by tachycardia [16] . Accordingly, sustained tachycardia and normal blood pressure were observed in clinical settings [17] . In addition, the Wells score and revised Geneva score that were developed to predict the probability of PTE have heart rate (>100 and ≥ 95 beats/min, respectively) as one of the predictive variables [8,9] .…”
Section: Discussionmentioning
confidence: 99%